Key elements of effective postgraduate GP educational environments: a mixed methods study. Issue 2 (15th February 2021) - Malau-Aduli, Bunmi S.; Alele, Faith O.; Heggarty, Paula; Reeve, Carole; Teague, Peta-Ann
Abstract : Objectives: Evidence in the literature suggests that satisfaction with postgraduate general practice (GP) training is associated with the quality of the educational environment. This study aimed to examine GP registrars' level of satisfaction with a distributed model of training in a regional educational environment and investigate the relationship between satisfaction and academic performance. Study design: A longitudinal 3-year study was conducted among GP registrars at James Cook University using a sequential explanatory mixed methods research design. GP registrars' satisfaction was obtained using the scan of postgraduate educational environment domains tool. A focus group discussion was conducted to explore GP registrars' perceptions of satisfaction with the educational environment. Setting: James Cook University General Practice Training (JCU GPT) programme. Participants: Six hundred and fifty one (651) GP registrars enrolled between 2016 and 2018 at JCU GPT programme. Results: 651 registrars completed the satisfaction survey between 2016 and 2018. Overall, 92% of the registrars were satisfied with the educational training environment. Registrars who had become fellows reported higher satisfaction levels compared with those who were still in training (mean=4.39 vs 4.20, p=0.001). However, academic performance had no impact on level of satisfaction with the educational environment. Similarly, practice location did not influence registrars' satisfaction rates. Four themes (rich rural/remote educational environment, supportive learning environment, readiness to continue with rural practice and practice culture) emerged from the thematic data analysis. Conclusion: A clinical learning environment that focuses on and supports individual learning needs is vital for effective postgraduate medical training. This study suggests that JCU GPT programme's distributed model fostered a satisfying and supportive training environment with rich educational experiences that enhance retention of GP registrars in rural/remote North Queensland, Australia. The findings of this study may be applicable to other settings with similar training models.